2014
DOI: 10.1155/2014/453085
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Assay of Vitamin B-2 (Riboflavin) in Alkaline Borate Buffer with UV/Visible Spectrophotometry

Abstract: The detection and assay of vitamin B-2 (riboflavin) was accomplished under aqueous conditions using sodium borate buffering at pH 7.52 conditions. The absorbance spectrum of riboflavin was determined at different pH values utilizing several buffers. The buffer at pH at 7.52 is followed by accurate and sensitive assay of riboflavin by spectrophotometer at 440 nm wavelength. Where indicated an origin solution (stock) was employed by dissolving sufficient vitamin to make a stock solution of 1.403 × 10−4 molar con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Furthermore, ribo avin also yields three absorption peaks between 250 to 500 nm at 270, 350, and 446 nm. Similar absorption peaks were also observed in ribo avin using sodium borate buffer at pH 7.52 (Bartzatt and Wol 2014). However, none of the other spectral peaks was found.…”
Section: Analysis Of Extracellular Respiration Pathwaysupporting
confidence: 79%
“…Furthermore, ribo avin also yields three absorption peaks between 250 to 500 nm at 270, 350, and 446 nm. Similar absorption peaks were also observed in ribo avin using sodium borate buffer at pH 7.52 (Bartzatt and Wol 2014). However, none of the other spectral peaks was found.…”
Section: Analysis Of Extracellular Respiration Pathwaysupporting
confidence: 79%
“…The nanoprobe provides a simple approach to creating a ratiometric fluorescent sensor based on the FRET process for the determination of RF in aqueous media. Capillary Electrophoresis/Laser-Induced Fluorescence 0.001-1.33 0.008 [15] HPLC/tandem mass spectrometry 0.011-53.1 0.029 [12] Ag nanoparticles modified with β-CD/Colorimetry 0.16-4.66 0.167 [36] Spectrophotometry/Absorbance at 440 nm 0.797-123 0.79 [11] Graphitic carbon nitride/Fluorimetry (FRET) 0.4-10 0.170 [16] Carbon-dot-codoped N, P/Fluorimetry (FRET) 0.5-50 0.170 [17] g-CNQDs@Zn-MOF/Fluorimetry (FRET) 0-1 0.015 [18] Sulfonated graphene/Fluorimetry (FRET) 0.4-10 1.6 [37] N,S-doped carbon dots/Fluorimetry (FRET) 0.56-7.4 1.9 [19] Graphene-PEG/Fluorescence Quenching 0-6.3 60 [38] Molecularly Imprinted Polymer (PIM)/Fluorimetry Not reported 79.7 [39] Carbon dots (N, COO − )/Fluorimetry (FRET) 0-11 0.025 This work…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…It has been reported that RF can also prevent different types of cancers [10]. Accordingly, the determination of RF has become very important and, therefore, different methods have been developed for the determination of RF, including spectrophotometric methods [11], high-performance liquid chromatography [12], electrochemical methods [13,14], and capillary electrophoresis [15]. However, these methods have multiple shortcomings, including a slow response, low selectivity, the use of a large amount of solvent, high-cost equipment, and laborious procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The beads were then separated from the riboflavin solution using a magnetic separator. Riboflavin was quantified using a plate reader (Infinite Pro M200 Tecan, Switzerland) at 440 nm (Bartzatt and Wol, 2014). The riboflavin concentration was determined based on a calibration curve.…”
Section: Methodsmentioning
confidence: 99%